Profil Bahan Perisa Kritis Halal dalam Peraturan BPOM No. 13/2020 - Sarah Fathia; Tjahja Muhandri; Nugraha Edhi Suyatma (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Flavors play a role as a determinant of the acceptability of food product. Halal certificate is a required document in Indonesia. Halal material requirements refer to SK11/Dir/LPPOM MUI/VI/20. This study aimed to obtain a profile of halal critical flavoring materials in BPOM regulation no. 13/2020 based on the document requirements for halal materials in LPPOM's SK11 and propose for non-critical halal flavoring materials. Materials used in this study were data-from BPOM regulation no. 13/2020, halal material requirements SK11/Dir/LPPOM MUI/VI/20 and other literatures associated with material production process information. The research method includes data collection based on CAS numbering, determination of BPOM flavoring materials outside the list of non-critical halal materials, determination of the production process for flavoring material, mapping of halal critical flavoring materials. The results showed that 53.82% (1381/2566) of the flavoring materials in BPOM regulations were halal critical materials. Based on identification results there were 26 types of production processes that have different halal critical sources that affect the required halal supporting documents. 65.38% (17/26) of critical halal sources came from raw materials, 30.77% (8/26) critical halal sources came from raw materials and manufacturing processes. The criticality of halal flavoring materials depends on the source of the raw material and the production process. Flavors obtained from the chemical synthesis process (414/1381) can be proposed as non-critical halal flavorings.